PATOLOGI EKSEKUSI KURIKULUM NASIONAL: TINJAUAN SISTEMATIS KESIAPAN SEKOLAH (KTSP - KURIKULUM MERDEKA) - Syamsi Jenar Savithra; Verzuwela Blezinsky Manihuruk (Smart Education, 2026)
Abstract: Education is a crucial foundation for development, yet system reforms are frequently impeded by the gap between policy theory and practical reality. This study presents a systematic review of national educational curriculum execution pathology, focusing on the transition from the School-Based Curriculum (KTSP) to the Emancipated Curriculum (Kurikulum Merdeka) in Indonesia. The primary issue explored is the structural, regulatory, and cultural gap between central government policy design and grassroots school ecosystem readiness. Utilizing a Systematic Literature Review (SLR) based on PRISMA 2020 guidelines, analysis was conducted on indexed international literature published between 2019 and 2026. Results reveal that curriculum implementation failures are frequently rooted in